SEJARAH DAN DAMPAK POSITIF EKONOMI DI SEKITAR MAKAM SYEKH MAULANA MAGHRIBI DESA WONOBODRO - Ayu Hartati (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2023)
Abtract Batang Regency, especially Blado Subdistrict, Wonobodro Village, there is a Religious Tourism in the form of a tomb which is known together that the tomb is the tomb of Sheikh Maulana Maghribi which is never lonely every day always visited by tourists or pilgrims, especially in the month of As-syuro. The tomb in Wonobodro is not only the tomb of Sunan Gresik, but also the founders of Wonobodro Village are buried side by side and surround the main tomb. Therefore, this study aims to understand the history of religious tourism in Wonobodro's tomb and the things that affect the economy from the impact of religious tourism on local residents. This research uses a qualitative research method. Regarding the location of the research, it was carried out in Wonobodro Village, Blado, Batang Regency. Then rather than that, this research focuses on the history of religious tourism and then things that affect the economy of the surrounding community with the existence of religious tourism. This study resulted in several discussions such as the existence of religious tourism to the tomb of Sheikh Maulana Maghribi including a form of respect for the residents around the tomb for him who gave a good, holy and sacred influence like auliya and scholars but no one knows the exact history clearly. Then the presence of the tomb in the midst of the Wonobodro residents also raised the economic level of the residents. The produce they use as the material they sell and buy is able to provide a hefty profit. This research also raises suggestions to the citizens and the government of Batang Regency to preserve and improve the optimization of religious tourism that was abandoned from ancient times as local culture and to explore more deeply how the exact history of religious tourism or the relics that are increasingly being abandoned here are increasingly being abandoned. Keywords: Wonobodro, Religious Tourism, Economic Influence.